An Interactive Family Tourism Decision Model. (January 2023) - Li, Mimi; Lin, Guyang; Feng, Xiaohong
To establish an interactive model reflecting how children's involvement in family tourism decisions interacts with internal and external factors, this study examines the interrelationships between children's individual characteristics (tourism knowledge and tourism attachment), parental characteristics (socio- and concept-orientation family communication patterns), and children's influence on family tourism decision making (initiation and search/decision stages) using structural equation modeling. Results reveal that tourism knowledge and socio- and concept-orientation patterns are positively related to children's influence on both decision stages. Specifically, tourism knowledge mediates relationships between socio- and concept-orientation patterns and children's influence on the initiation stage; tourism attachment mediates the relationship between the concept-orientation pattern and children's influence on the initiation stage. Lastly, theoretical and managerial implications of these findings are discussed.